Location-based messaging using an RFID-based access control system - Lacap, Maria Elvira Tan Sacro; Dizon, Joeven Rex Lagman (2009.)
Nearly all companies that deal with confidential resources use some form of access control system to limit physical access to authorized persons only. Due to reduction in cost of production, radio frequency identification devices are now the common technology for such applications. In this paper, we show the use of this technology for an access control system with an electronic door lock that can be used in a typical workplace environment. However, in contrast to commercially available systems that are based on proprietary and closed technology, our access control system is based on accepted industry standards and secure and open platforms. To demonstrate the flexibility and extensibility that our standards-based approach provides, we designed, developed and implemented a location-based messaging and an electronic in/out board with a flexible and enhanced user interface connected to the access control system. Location-based messaging was achieved with the use of an open platform. The development of the graphical user interface that successfully displays status of users as dictated by their input to the RFID card reader is discussed in this paper. In contrast to the initial plan, the implementation of the electronic door lock was not done in an open platform due to some problems encountered. These problems are also discussed in this paper.
Thesis (B.S. Computer Engineering)--University of the Philippines, Diliman.
Keywords: Security systems; Radio frequency identification systems; Access control systems; RFID